2011
DOI: 10.1016/s1015-9584(11)60022-5
|View full text |Cite
|
Sign up to set email alerts
|

Cause and Management of Recurrent Primary Spontaneous Pneumothorax After Thoracoscopic Stapler Blebectomy

Abstract: In thoracoscopic stapler blebectomy for primary spontaneous pneumothorax, the most common cause of recurrence was new bulla formation. It is necessary to establish additional procedures involving either the visceral pleura or the parietal pleura to reduce the recurrence rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 25 publications
1
9
0
2
Order By: Relevance
“… 29 The importance of pleurodesis was further stressed by some reports showing the increasing risk of postoperative recurrent pneumothorax due to incomplete resection of bullae 10 or bulla regrowth along staple-lines, 30 and the pleural porosity theory proposed by Noppen et al as a remaining etiology of PSP; 31 in both, the recurrence could be lowered by pleurodesis. 23 , 32 Our study supported that pleurodesis is an independent risk factor in multivariate analysis for the prevention of postoperative pneumothorax recurrence. The majority of our pleurodesis method, a combination of intraoperative mechanical pleurodesis (pleural abrasion) with chemical pleurodesis (by Talc poudrage or minocycline slurry), is a process of evolution and inspiration by the prospective randomized trial by Chen et al 33 in 2006 showing that additional minocycline pleurodesis could significantly lower the recurrence rate after VATS in PSP but with increased immediate chest pain.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“… 29 The importance of pleurodesis was further stressed by some reports showing the increasing risk of postoperative recurrent pneumothorax due to incomplete resection of bullae 10 or bulla regrowth along staple-lines, 30 and the pleural porosity theory proposed by Noppen et al as a remaining etiology of PSP; 31 in both, the recurrence could be lowered by pleurodesis. 23 , 32 Our study supported that pleurodesis is an independent risk factor in multivariate analysis for the prevention of postoperative pneumothorax recurrence. The majority of our pleurodesis method, a combination of intraoperative mechanical pleurodesis (pleural abrasion) with chemical pleurodesis (by Talc poudrage or minocycline slurry), is a process of evolution and inspiration by the prospective randomized trial by Chen et al 33 in 2006 showing that additional minocycline pleurodesis could significantly lower the recurrence rate after VATS in PSP but with increased immediate chest pain.…”
Section: Discussionsupporting
confidence: 76%
“…Reviewing the literature, several factors have been shown to be associated with the postoperative recurrence in patients with PSP, including young age, 22 , 23 current smoker, 24 missed or incomplete bullectomy, 22 and prolonged postoperative air-leak. 25 Subpleural blebs and bullae are commonly found in the lung apices during thoracoscopy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that recurrence rates were higher than expected. There are publications indicating that 90% of the patients treated with thorascoscopic blebektomi, but not the ones treated with pleurodesis, within the first two years, recurrence rate, especially in young bilateral spontaneous pneumothorax patients’ group, has much developed new bül formation in postoperative stapler line, and recurrent pneumothorax rate is higher with traditional surgery method (17). According to the data from the literature, in order to reduce the recurrent rate in primary spontaneous pneumothorax and video assisted thoracic surgery, apical resections as well as apical pleurectomy procedures are recommended (18).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with disorders of blood sugar control have a greater relative risk for the development of lung cancer. [ 18 ] The growth hormone/insulin like growth factor 1 (IGF-1) axis is considered to contribute to this finding. [ 19 ] IGF-1 is secreted by stimulation of growth hormone, and combines with insulin-like growth factor binding protein-3 in the circulation.…”
Section: Discussionmentioning
confidence: 99%